(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The fundamental parameters of natural semiconductor fibers, the dependence of electrical conductivity on temperature, and the photoconductivity of doped semiconductor bamboo fibers have been studied. The temperature dependences of the current-voltage characteristics and the electrical conductivity of bamboo doped and undoped with iodine were studied to create new elements of electronic equipment